I Am Malala : How One Girl Stood up for Education and Changed the World - Yousafzai, Malala, 1997-; McCormick, Patricia, 1956- (New York : Little, Brown and Company, 2016)
"I Am Malala. This is my story. Malala Yousafzai was only ten years old when the Taliban took control of her region. They said music was a crime. They said women weren't allowed to go to the market. They said girls couldn't go to school. Raised in a once-peaceful area of Pakistan transformed by terrorism, Malala was taught to stand up for what she believes. So she fought for her right to be educated. And on October 9, 2012, she nearly lost her life for the cause: She was shot point-blank while riding the bus on her way home from school. No one expected her to survive. Now Malala is an international symbol of peaceful protest and the youngest ever Nobel Peace Prize nominee. In this Young Readers Edition of her bestselling memoir, which includes exclusive photos and material, we hear firsthand the remarkable story of a girl who knew from a young age that she wanted to change the world -- and did. Malala's powerful story will open your eyes to another world and will make you believe in hope, truth, miracles and the possibility that one person -- one young person -- can inspire change in her community and beyond."--
Part One. Before the Taliban. As free as a bird ; Dreams ; A magic pencil ; A warning from God ; The first direct threat -- Part Two. A shadow over Our Valley. Radio Mullah ; The Taliban in Swat ; No one Is safe ; Candy from the sky ; 2008: What terrorism feels like -- Part Three. Finding my voice. A chance to speak ; A schoolgirl's diary ; Class dismissed ; Secret school ; Peace? ; Displaced ; Home ; A humble request and a strange peace ; Good news at last -- Part Four. Targeted. A death threat against me ; The promise of spring ; Omens ; A day like any other -- Part Five. A new life, far from home. A place called Birmingham ; Problems, solutions ; A hundred questions ; Passing the hours ; We are all here now ; Filling in the blanks ; Messages from around the world ; A bittersweet day ; Miracles ; This new place ; The one thing we all know ; Anniversary ; One girl among many -- Epilogue: October 2015
"Winner of the Nobel Peace Prize"--Cover
"First published in hardcover in August 2014 by Little, Brown and Company"--Title page verso
Accelerated Reader AR
Keywords: Yousafzai, Malala, -- 1997- -- Juvenile literature; Yousafzai, Malala, -- 1997- -- Juvenile literature; Young women -- Education -- Pakistan -- Biography -- Juvenile literature; Children's rights -- Pakistan -- Juvenile literature; Young women -- Education -- Pakistan; Children's rights -- Pakistan; Women -- Biography; Biographies